Қамқорлық жəне қамқоршылық туралы қазақстандық заңнаманың объективті өзгерісінің алғышарттары (Journal of actual problems of jurisprudence, 2019)
In this article explores the reasons of change of the legislation on guardianship and custody in Kazakhstan